Socio-demographic patterning of objectively measured physical activity and sedentary behaviours in eight Latin American countries: Findings from the ELANS study - Ferrari, Gerson Luis de Moraes (2019)
Physical activity (PA) and sedentary behaviours (SB) are two independent risk factors for non-communicable diseases. However, there is a lack of objectively measured information on PA and SB in low- and middle-income countries. The aim of this study was to use objective data to characterise socio-demographic patterns of PA and SB in eight Latin American countries. 2732 participants (aged 15-65 years) from the Latin American Study of Nutrition and Health (ELANS) were included. PA and SB data were collected using accelerometers. Overall and country-specific average levels of time spent in PA and SB were compared by sex, age, socioeconomic and education level. Overall, the mean time spent in SB was 571.6 min/day, ranging from 553.8 min/day in Chile to 596.7 min/day in Peru. Average levels of light, moderate-to-vigorous physical activity (MVPA) and total PA were 311.1 min/day (95% CI: 307.7; 314.5), 34.9 min/day (95% CI: 34.0; 35.9) and 7531.2 MET-min/week (95% CI: 7450.4; 7611.9), respectively. MVPA and total PA were higher in men than women. The prevalence of physical inactivity was 40.6%, ranging from 26.9% (Chile) to 47% (Costa Rica and Venezuela). Women were more physically inactive than men (47.7% versus 33.0%). SB levels were highest among those with higher education; PA graded positively with socioeconomic level. Our findings can inform the planning of health policies and programmes designed to reduce levels of physical inactivity, as well as inform the local and cultural adaptation of these policies and programmes for implementation in Latin America. Highlights Worldwide studies of physical activity (PA) and sedentary behaviours (SB) have historically under-represented Latin American countries due to the lack of surveillance data. Across eight Latin American countries, the ELANS study collected data on PA and SB using an objective method (accelerometers) which we have analysed to quantify and characterise socio-demographic patterns. Over four-in-ten participants were physically inactive (40.6%); with a gender gap (47.7% women; 33.0% men); and striking differences between countries (47% Costa Rica and Venezuela; 26.9% Chile). In all countries, levels of moderate-to-vigorous physical activity (MVPA) were lowest, and levels of SB were highest, among participants in the higher education groups. Our findings on the unequal distribution of PA and SB increases the evidence base and can help to inform future intervention strategies in Latin America.